Ectopic Fetal Maceration With Uterine Rupture In A Non-Descriptive Bitch- A case report - J.Umamageswari; B. Prakash Krishna2; M.G. Mohammed Ali; S.Rangasamy; R.Sureshkumar; K.Ravikumar; R.Ranjini (The Indian Veterinary Journal, 2026)
A three years old, non-descriptive bitch was presented with the complaint of inappetence and abdominal distension for 20 days and whelped a month back. Ultrasound examination revealed mixed echogenicity fluid in the abdomen with hyperechoic foetal bone and radiography revealed radiopaque foetal bones in the ventral abdomen. Based on ultrasound examination and abdominal radiography, the case was confirmed as ectopic foetal maceration. An emergency laparotomy surgery was done, ascitic fluid was drained, macerated foetal parts were removed and the ruptured uterus was managed by bilateral ovariohysterectomy.